(untitled) (African Journal of Biomedical Research, 2021)
Background: The increase in cancer prevalence rate worldwide is a public health concern. Studies have recognized the use of phytomedicines in cancer treatment but their safety data is deficient. Vernonia amygdalina Delile (VA), Carica papaya Linn (CP) , and dihydroartemisinin (DHA) have been previously reported to have anti-cancer activities but their safety profiles when combined have not been validated. Materials and methods: Pilot toxicity study was carried out to determine doses for acute and sub-chronic toxicity studies of the two combined plant extracts and compound in albino mice (n=10) and Wistar rats (n=18). The experiment was done based OECD guidelines. Animals were dosed with 500, 1,000 and 2,000 mg/kg of drug combinations and observed for 24 hours and 90 days. Hematological, biochemical parameters and histopathological changes of liver and kidney were evaluated. Results: Drugs administration up to 5, 000 mg/kg did not cause mortality ( LD50 > 5, 000mg/kg) and concentrations of 2,000 mg/kg (acute study) did not show observed toxicity. There was no significant difference in body weight between the treated and control animals in 90 days study although there were observed significant differences in some hematology and biochemistry parameters. Histopathological examination of the liver and kidney did not reveal organ alterations. Conclusions: Although there were significant changes in hematological and biochemistry parameters, based on all results analysis and OECD classification of formulas as category 5, studied combinations might not cause known toxicity.